Timber and concrete composite system: A numerical and experimental approach for high temperatures - Molina, Julio Cesar [UNESP]; Calil Junior, Carlito (FapUNIFESP (SciELO), 2018)
The aim of this work was the evaluation of the temperature profile in two composite timber and concrete beam with cross-section T and metallic connection system subjected to high temperatures. The connection system, in this case, was performed by use of steel bars with 12.5 mm diameter, equally spaced, along the concrete-timber interface. The cross section T of the beam consisted of a timber piece with dimensions 5 cm x 15 cm connected of a concrete slab with 30 cm x 5 cm. To the composite beams, a total time of fire exposure equal to 40 minutes was considered. The numerical modeling of the system was carried out using the ANSYS software [1], version 10.0. The results of numerical simulations were compared with the experimental results of temperature obtained by the two composite beam, which were instrumented with thermo-couples and subjected to high temperature in a horizontal furnace constructed on EESC/USP for this purpose. The numerical and experimental results showed good agreement in this case. As a result, the temperature profiles are shown in cross section for various heating times and all numerical modeling strategy and the finite element used to determine the temperature profiles.
Sistema misto de madeira e concreto: Uma abordagem numérico e experimental para altas temperaturas
Keywords: Experimental analysis; Fire; Numerical simulation; Timber and concrete composite beam